2016
DOI: 10.15390/eb.2016.6218
|View full text |Cite
|
Sign up to set email alerts
|

Examining The Relationship Between Distributed Leadership and Organizational Trust According to Opinions of Teachers

Abstract: Öz Anahtar KelimelerBu araştırmada dağıtılmış liderlik ile örgütsel güven arasındaki ilişki, öğretmen görüşlerine dayalı olarak incelenmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…They purport that DL among school administrators may affect positively the perceptions of trust among teachers and is a key predictor of OT. The same result was highlighted by Adiguzelli (2016) and Algan and Ummanel (2020). Kilicoglu (2018) reported that DL contributes to the implementation of positive changes focused on the renewal of practices and improves the OT within schools.…”
Section: Mediating Role Of Organizational Trust Between Distributed Leadership and Knowledge Sharingmentioning
confidence: 57%
See 1 more Smart Citation
“…They purport that DL among school administrators may affect positively the perceptions of trust among teachers and is a key predictor of OT. The same result was highlighted by Adiguzelli (2016) and Algan and Ummanel (2020). Kilicoglu (2018) reported that DL contributes to the implementation of positive changes focused on the renewal of practices and improves the OT within schools.…”
Section: Mediating Role Of Organizational Trust Between Distributed Leadership and Knowledge Sharingmentioning
confidence: 57%
“…As a matter of fact, we hypothesize that OT may mediate the link between DL and tacit and explicit KS because on the basis of the above literature review, we postulated that DL is associated with OT (H5) which in turn may boost explicit KS (H6.a) and tacit KS (H6.b). Many scholars highlighted that DL is associated to OT within educational institutions (Adiguzelli, 2016;Beycioglu et al, 2012). Although this link lacks empirical studies within business firms, through a literature review, DL may promote OT in building an empowering climate in which multiple leaders can collaborate together and develop trust-based relationships within firms (Drescher et al, 2014;von Krogh et al, 2012).…”
Section: H6bmentioning
confidence: 99%
“…The roots of distributed leadership refer Gibb's (1947Gibb's ( , 1954 studies, while the researchers focused on its theoretical background only in 1990s (Archer, 1995;Bennett et al 2003a, b;Elmore, 2000;Fielding, 1999;Gronn, 2000;MacBeath et al 2004;Mahoney & Moos, 1998;Spillane, 2005;Spillane, Halverson & Diamond, 2001;Wallace & Hall, 1994;Woods et al 2004); and it became a subject of empirical studies in 2000's (Chen, 2007;Davis, 2009;ESHA, 2013;Gordon, 2005;Grenda, 2011;Heck & Hallinger, 2009;Singh, 2014;Smith, 2007;Williams, 2011). Specifically, in the Turkish literature, theoretical aspects of distributed leadership have been studied by a limited number of researchers (Baloğlu, 2011a(Baloğlu, , 2011b and its empirical aspects have been studied more as a scale adaptation with a limited number of scale development attempts and will become a subject for certain thesis dissertations (Adıgüzelli, 2016;Ağırdaş, 2014;Arabacı, Karabatak & Polat, 2016;Baloğlu, 2012;Kılınç, 2014;Korkmaz & Gündüz, 2011;Özdemir, 2012;Özkan & Çakır, 2017;Yılmaz & Turan, 2015). As a result of the literature review, it was seen that there is no study to determine the elements that support and prevent the implementation of distributed leadership within the school.…”
Section: Introductionmentioning
confidence: 99%
“…A brief literature review shows that numerous studies have been carried out on school structure, distributed leadership and accountability. In this context, the school structure has been examined in terms of academic optimism (Anderson, 2012;Çalık & Tepe, 2019;Messick, 2012;Özdemir & Kılınç, 2014), school climate (Jacob, 2003;Mayerson, 2010), school effectiveness (Çalık & Tepe, 2019;Koohi et al, 2019;Mayerson, 2010), organizational support (Çokyigit, 2020), organizational citizenship (Alev, 2019;Messick, 2012), teacher professionalism (Cerit, 2012, teacher self-efficacy (Kılınç et al, 2016), teachers' career satisfaction (Koohi et al, 2019), awareness and teacher empowerment (Watts, 2009), teachers' proactive behaviors (Cerit & Akgün, 2015), student success (Anderson, 2012), organizational trust (Çokyigit, 2020), collective student trust (Koster, 2016), organizational silence (Bozkuş et al, 2019;Demirtaş et al, 2016), school principals' leadership styles (Buluç, 2009), organizational cynicism (Demirtaş, et al, 2016), organizational health (Ordu & Tanrıöğen, 2013), job satisfaction (Bozkuş et al, 2019 In addition, distributed leadership has been examined in terms of organizational commitment (Aboudahr & Jiali, 2019;Akdemir & Ayık, 2017;Yetim, 2015), organizational trust (Adıgüzelli, 2016;Çiçek, 2018;Yılmaz, 2014), teacher motivation (Wahab et al, 2013), teacher self-efficacy (Halim & Ahmad, 2016;Kurt, 2016), organizational citizenship (Çakır, 2019;…”
Section: Introductionmentioning
confidence: 99%